2013
DOI: 10.1073/pnas.1318247110
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of anti-inflammatory and antioxidant activities of exemestane and synergism with sulforaphane for disease prevention

Abstract: Exemestane (6-methyleneandrosta-1,4-diene-3,17-dione) is a synthetic steroidal inhibitor of the aromatase reaction that catalyzes the terminal and rate-limiting step of the biosynthesis of estrogens. It is active clinically in preventing, delaying progression of, and treating mammary cancers, many of which are estrogen receptor-positive. A striking feature of the structure of exemestane is an extended system of conjugated Michael reaction functions, which is also characteristic of inducers of a broad network o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…Sulforaphane also exhibits anti-inflammatory properties. For example, free sulforaphane has exhibited concentrationdependent attenuation of bacterial lipopolysaccharide-induced expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2 and synthesis and secretion of proinflammatory cytokines [69,70]. In a model of osteoarthritis, sulforaphane has attenuated interleukin (IL)-1b potentiation of the expression of tissue-degrading A disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS4) (aggrecanase-1), ADAMTS5 (aggrecanase-2), matrix metalloproteinase (MMP)-1, and MMP13 in primary human articular chondrocytes following sulforaphane uptake into these cells [71].…”
Section: Direct Actionsmentioning
confidence: 99%
“…Sulforaphane also exhibits anti-inflammatory properties. For example, free sulforaphane has exhibited concentrationdependent attenuation of bacterial lipopolysaccharide-induced expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2 and synthesis and secretion of proinflammatory cytokines [69,70]. In a model of osteoarthritis, sulforaphane has attenuated interleukin (IL)-1b potentiation of the expression of tissue-degrading A disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS4) (aggrecanase-1), ADAMTS5 (aggrecanase-2), matrix metalloproteinase (MMP)-1, and MMP13 in primary human articular chondrocytes following sulforaphane uptake into these cells [71].…”
Section: Direct Actionsmentioning
confidence: 99%
“…Exogenous compounds, including allyl isothiocyanate (AITC), and endogenously generated reactive oxygen species (ROS) and their derivatives, have been identified as TRPA1 agonists (9)(10)(11)(12). Similar to other reactive agonists (7), highly electrophilic conjugated Michael acceptor groups of exemestane (13) and nitrile moieties of letrozole and anastrozole (14) react with the thiol groups of specific cysteine and lysine residues to trigger TRPA1 and activate nociceptors (8).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies utilizing cell culture models revealed a synergism between sulforaphane and modulators of estrogen receptor signaling including 17β-Estradiol and exemestane, an aromatase inhibitor, although the underlying mechanism(s)remain(s) undefined (Angeloni et al, 2017, Liu and Talalay, 2013). Since ER-β reportedly exerts a positive impact on NRF2 signaling, we performed topical treatments of SF in combination with pre-treatment intra-peritoneal injections of diarylpropionitrile (DPN), an ER-β selective agonist that has been shown to also oppose ER-α activity (Song and Pan, 2012).…”
Section: Resultsmentioning
confidence: 99%